Peran Orang Tua Dalam Mendorong Prestasi Non Akademik Siswa Di SDN Balongbesuk Jombang - Usthufiyah, Farida; Fitra Raharja , Hawwin; Dwinata, Anggara (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The family, particularly parents, plays a pivotal role in instilling life values in their children to achieve meaningful life goals. This study aims to explore parental parenting styles concerning non-academic achievements among students at SDN Balongbesuk Jombang. A qualitative case study approach was employed, utilizing data collected through observation, interviews, and documentation. Parents of non-academic achievers and the students themselves served as data sources. The findings reveal that parents employ a